ANALYSING GROUP DIFFERENCES IN INTELLIGENCE USING THE PSYCHOMETRIC META-ANALYTIC METHOD OF CORRELATED VECTORS HYBRID MODEL: A REPLY TO WICHERTS (2018) ATTACKING A STRAWMAN. Issue 6 (17th July 2018) - te Nijenhuis, Jan; van den Hoek, Michael
Summary: Wicherts (2018) criticizes the use of the method of correlated vectors when testing Spearman's hypothesis. It is argued that Wicherts ignores the psychometric meta-analytic method of correlated vectors hybrid model and so is attacking a strawman.